Influence of Starkeya novella on Mechanical and Microstructural Properties of Cement Mortars - Onesmus Mulwa Munyao; Joseph Karanja Thiong’o; Jackson Muthengia Wachira; Daniel Karanja Mutitu; Romano Mwirichia (Journal of Chemistry)
Cement-based materials are subject to degradation during their service life. Most of the structural failures have been associated with corrosion of the rebar due to chloride ingress, alkali aggregate reaction, and/or sulfate attack. Microbial activities, especially in waste water collection points such as sewer lines, may compromise the integrity of concrete structures. This study reports an experimental work carried out to determine the effect of Starkeya novella bacteria species on mechanical and microstructural properties of cement mortars. Mortar prisms were prepared from selected ordinary Portland cement (OPC) and Portland pozzolana cement (PPC) in Kenyan markets. Bacterial solution of 1.0 × 107 cell/mL concentration was used as either mix water, curing media, or both. Distilled water was used to prepare mortar prisms for control samples. Compressive strength was determined after the 7th, 28th, 56th, and 90th day of curing. Scanning electron microscopy (SEM) was tested on both bacterial and control mortar prisms after the 28th day of curing. Both PPC and OPC exhibited significant decrease in compressive strength for bacterial-prepared mortars as compared to controls. SEM analysis showed extreme erosion on the microstructure of the microbial mortars. This was denoted by massive formation of ettringite and gypsum which are injurious to mortar/concrete.